Upogibna trdnost in togost slojnatega furnirnega lesa (LVL) iz termično modificirane in nemodificirane bukovine - Saražin, Jaša (Les (Ljubljana), 2017)
The aim of the research was to define and develop a wooden composite with a thin cross-section and which could be used as reinforcement material in oversized wooden window profiles. An additional limitation was to bond the composite at room temperature. Based on a review of the literature, laminated veneer lumber (LVL) was chosen as the best option. The researched LVL samples were made of 0.5 mm thick, cut, beech (Fagus sylvatica L.) veneer, bonded with polyurethane adhesive (Purbond HB 440). Half of the samples were made of thermally modified veneers, and other half of unmodified. Bending strength and stiffness were determined with a three-point bending test. Thermally modified samples had on average 19 % lower bending strength compared to the unmodified samples, but the modulus of elasticity (stiffness) did not change significantly. The bending strength of up to 150 MPa was satisfactory, but the modulus of elasticity of 13 GPa was far below expectations. This is attributed to the selection of too thin veneer and too low bonding temperature, which does not enable densification of the composite
Keywords: beech; bending strength; bukev; furnir; LVL; modul elastičnosti; modulus of elasticity; termična modifikacija; thermal modificaton; upogibna trdnost; veneer